An evaluation of a public-private partnership as an alternative delivery mechanism to enable the effective redistribution of land in KwaZulu-Natal : the case of Inkezo Land Company - Madhanpall, Anwhar (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MPA (School of Public Management and Planning))--University of Stellenbosch, 2008.